2016
DOI: 10.1016/j.molmet.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ATP citrate lyase in pancreatic beta cells does not inhibit insulin secretion or glucose flux and implicates the acetoacetate pathway in insulin secretion

Abstract: ObjectiveGlucose-stimulated insulin secretion in pancreatic beta cells requires metabolic signals including the generation of glucose-derived short chain acyl-CoAs in the cytosol from mitochondrially-derived metabolites. One concept of insulin secretion is that ATP citrate lyase generates short chain acyl-CoAs in the cytosol from mitochondrially-derived citrate. Of these, malonyl-CoA, is believed to be an important signal in insulin secretion. Malonyl-CoA is also a precursor for lipids. Our recent evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Similarly, the ACL inhibitor hydroxycitrate lacked effect on GSIS in INS1(832/13) cells and rat islets [68]. In 13 C isotopomer flux measurements, inhibiting the flux of glucose carbons into malonyl-CoA by hydroxycitrate had no effect on GSIS in INS1 cells [40]. Finally, the use of the FA-CoA synthase inhibitor, triascin C, did not reveal a modification of GSIS in INS-1 cells [69] or INS 832/13 cells [70].…”
Section: Inhibition Of Fatty Acid Oxidation By Bromopalmitatementioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, the ACL inhibitor hydroxycitrate lacked effect on GSIS in INS1(832/13) cells and rat islets [68]. In 13 C isotopomer flux measurements, inhibiting the flux of glucose carbons into malonyl-CoA by hydroxycitrate had no effect on GSIS in INS1 cells [40]. Finally, the use of the FA-CoA synthase inhibitor, triascin C, did not reveal a modification of GSIS in INS-1 cells [69] or INS 832/13 cells [70].…”
Section: Inhibition Of Fatty Acid Oxidation By Bromopalmitatementioning
confidence: 91%
“…Suppression of ACL ACL knockdown was reported to have no effect on GSIS in INS-1(832/13) cells when measured only at maximal 16.7 mmol/l glucose, possibly due to the absence of NEFA in the incubation medium for insulin secretion as well as GSIS not being tested at submaximal glucose [68]. The lack of effect could also be due to the presence of alternate routes that provide cytosolic acetyl-CoA, as mentioned above [40]. We reported that ACL knockdown in the same cell line under similar experimental conditions does result in reduced GSIS but that the inhibitory effect is most prominent in the presence of exogenous NEFA or at intermediate glucose [34].…”
Section: Inhibition Of Fatty Acid Oxidation By Bromopalmitatementioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic bacterial fermentation of complex polysaccharides yields butyrate, which is absorbed by colonocytes in mammalians for terminal oxidation or ketogenesis (Cherbuy et al, 1995), which may play a role in colonocyte differentiation (Wang et al, 2016). Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…For example, altered acetylation of proteins in the glycolytic pathway and tricarboxylic acid cycle, as in the ACC-null liver [20], may impair metabolic coupling in ACC1-null beta cells. Likewise, acetoacetate breakdown provides acetyl-CoA to ACC1 in beta cells via a pathway distinct from ATP citrate lyase [45]. It is therefore plausible that loss of ACC1 activity could result in persistent elevations of acetoacetate, contributing to defective beta cell function in βACC1KO and tmx-βACC1KO mice.…”
Section: Discussionmentioning
confidence: 99%